2014
DOI: 10.1038/srep04723
|View full text |Cite
|
Sign up to set email alerts
|

Gellan sulfate inhibits Plasmodium falciparum growth and invasion of red blood cells in vitro

Abstract: Here, we assessed the sulfated derivative of the microbial polysaccharide gellan gum and derivatives of λ and κ-carrageenans for their ability to inhibit Plasmodium falciparum 3D7 and Dd2 growth and invasion of red blood cells in vitro. Growth inhibition was assessed by means of flow cytometry after a 96-h exposure to the inhibitors and invasion inhibition was assessed by counting ring parasites after a 20-h exposure to them. Gellan sulfate strongly inhibited invasion and modestly inhibited growth for both P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 53 publications
1
16
0
1
Order By: Relevance
“…However, other sulphated polysaccharides, including heparin, fucoidan, and dextran sulfate [ 28 , 29 ] have shown promising in vitro anti-malarial activity. An example is the previous report on gellan sulfate [ 30 ] that demonstrated that chemical modification, namely, sulphation, could change the characteristics of these compounds. Given that these polysaccharides are still considered promising potential anti-malaria drugs, chemical modification might decrease the side effects of such compounds.…”
Section: Discussionmentioning
confidence: 99%
“…However, other sulphated polysaccharides, including heparin, fucoidan, and dextran sulfate [ 28 , 29 ] have shown promising in vitro anti-malarial activity. An example is the previous report on gellan sulfate [ 30 ] that demonstrated that chemical modification, namely, sulphation, could change the characteristics of these compounds. Given that these polysaccharides are still considered promising potential anti-malaria drugs, chemical modification might decrease the side effects of such compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, sulfated polysaccharides have been analyzed as drug candidates for protozoan infectious diseases [ 3 , 85 , 86 ]. According to our data, the sulfated positions in the carbohydrates can be critical for the inhibitory quality [ 3 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In vitro invasion assay. The invasion assay was conducted according a previous method (24). P. falciparum was cultured in RPMI-1640 medium supplemented with 10% human serum and erythrocytes (2% hematocrit) at 37˚C and then flushed with a gas mixture containing 5% O 2 , 5% CO 2 and 90% N 2 .…”
Section: Expression and Purification Of The Pftip-gst Proteinmentioning
confidence: 99%